Intervention of Sanguniang Barangay Gulod Novaliches, Quezon City Againts Streetcrime: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study represents how to mitigate street crimes in Barangay Gulod Novaliches QuezonCity and provides an opportunity for the citizens of Barangay Gulod. It represents the solutionto the insufficiency of the Barangay that can help the staff of the Barangay Officials do theirduty. The aim of the researchers is to know what the most effective crime prevention methodsare. This research can help the peace officer or the Public Officer maintain Peace and Order inthe Barangay. The community can also benefit from This study on how to protect themselvesfrom street crimes.To Sanguniang Barangay Gulod, The Researchers highly recommend focusing on sports andtournaments, which can be an effective Barangay Activity in promoting peace and order and,eventually, crime mitigation. The Researchers highly recommend foot patrol to monitor theeffective implementation of curfew hours within the LGU jurisdiction. Future ResearchersUnderstand well the effect and influence that will happen depending on the other parametersthat can be connected to different classifications of crime intervention.
Keywords: Criminology